From Juan Ambrosio Huerta to Mariano Holguín : Episcopacy, ultramontanism and modernity in Arequipa (1880-1930) - Iberico Ruiz, Rolando (2020)
In Peru, while the liberal sectors in Lima were gaining presence, Arequipa became a bastion city of Catholicism. In this process, the episcopacy played a key role as a catalyst of spaces of ultramontane formation for the clergy and the laity, of promotion of lay apologetic and social societies, of consolidation of pious practices and of construction of public legitimacy for the Church in the city. In this sense, this article studies the consolidation process of ultramontanism and social Catholicism among the episcopates of José Ambrosio Huerta, Manuel Ballón and Mariano Holguín. Hence, the Church strengthened its presence in the regional public space and was able to articulate discourse on modernity from the Catholic perspective, in favor of the public presence of the Church as the structuring of political, social and moral life in the city.